Factors Affecting Students’ Behavioral Intention to Use LMS at a Turkish Post-Secondary Vocational School - Cigdem, Harun; Ozturk, Mustafa (International Review of Research in Open and Distributed Learning, 2016)
There is a substantial increase in the use of learning management systems (LMSs) to support teaching and learning activities in higher education institutions. Despite their benefits, students use them to a limited extend due to a number of factors influencing behaviors. This study executed a three-tier use model to examine the predictors of students’ behavioral intention to use LMSs at a two-year post-secondary military school in Turkey, and the participants consisted of 155 students. The data were collected through an online questionnaire and analyzed through Pearson correlation coefficients and linear regression analyses. Results showed that multimedia instruction had a direct influence on perceived usefulness and perceived ease of use, while interactivity had a direct influence only on perceived satisfaction. Perceived satisfaction was also affected by perceived usefulness and perceived ease of use. Perceived ease of use exerted a direct influence on perceived usefulness, as well. Moreover, perceived usefulness had a great influence on behavioral intention to use LMSs. As a final point, self-efficacy did not take a position in the model due to its insignificant relationships with the other constructs. It is suggested that an increase in the multimedia features and interactivity of the system could lead to higher perceived usefulness and ease of use among learners, and both factors add to learners’ perceived satisfaction which in turn increases their engagement.